The relevance of social contexts and social action in reducing substance use and victimization among women participating in an HIV prevention intervention in Cape Town, South Africa - Reed E; Emanuel AN; Myers B; Johnson K; Wechsberg WM (Dove Medical Press, 2013)
Elizabeth Reed,1 Andrea N Emanuel,2 Bronwyn Myers,3,4 Kim Johnson,3 Wendee M Wechsberg2,5–7 1George Washington University School of Public Health, Department of Prevention and Community Health, Washington, DC, USA; 2RTI International, Research Triangle Park, NC, USA; 3Alcohol and Drug Abuse Research Unit, Medical Research Council, Cape Town, South Africa; 4Department of Psychiatry and Mental Health, University of Cape Town, Cape Town, South Africa; 5Gillings Global School of Public Health, University of North Carolina, Chapel Hill, NC, USA; 6Psychology in the Public Interest, North Carolina State University, NC, USA; 7Psychiatry and Behavioral Sciences, Duke University School of Medicine, NC, USA Objectives: To examine qualitatively how women's social context and community mobilization (eg, mobilizing women to take social action and engaging their community in social change) influence substance use abstinence and victimization among women participating in a human immunodeficiency virus (HIV) intervention in Cape Town, South Africa. Methods: Thirty women who had participated in a randomized controlled trial of a group-delivered intervention to address substance use, gender-based violence, and associated risk for HIV (The Women's Health CoOp) were selected to participate in semi-structured interviews about their perceived impact of the intervention on their substance use and exposure to victimization. The Women's CoOp intervention involved creating a new positive social environment for women within a group setting that also fostered women's social action (eg, educating peers or family members) in the community. Interviews were analyzed using content analysis and coded to examine women's descriptions of social contexts and social action, and the influence of these on women's substance use abstinence and exposure to victimization. Results: Social support (eg, via program staff and other participants) and social action (eg, engaging others in the community on issues relevant to substance use prevention or other health topics) promoted within the program, as well as outside social influences within women's life contexts (eg, support from non-substance using family or male partners, leaving male partners or other peer relationships characterized by drug use, or finding employment) were key factors reported by women in terms of facilitating their substance use abstinence and in reducing women's exposures to victimization. Conclusion: Findings highlight the potential for group-delivered interventions that include mobilizing women to take social action in the larger community to be effective approaches for facilitating substance use abstinence, reductions in victimization, and ultimately, to address the intersection between substance use, violence, and HIV risk among women in this high HIV prevalence setting. Keywords: HIV prevention, substance use, social context, women